Dipeptidyl Peptidase-4 Inhibitors versus Other Antidiabetic Drugs Added to Metformin Monotherapy in Diabetic Retinopathy Progression: A Real World-Based Cohort Study - Chung, Yoo-Ri; Ha, Kyoung Hwa; Kim, Hyeon Chang; Park, Sang Jun; Lee, Kihwang; Kim, Dae Jung (Diabetes & metabolism journal, 2019)
To investigate the effects of dipeptidyl peptidase-4 inhibitor (DPP4i) as add-on medications to metformin on progression of diabetic retinopathy (DR) in patients with type 2 diabetes mellitus, compared with sulfonylurea (SU) or thiazolidinedione (TZD). We identified 4,447 patients with DPP4i, 6,136 with SU, and 617 with TZD in addition to metformin therapy from the database of Korean National Health Insurance Service between January 2013 and December 2015. Cox proportional hazards regression models were used to calculate hazard ratios (HRs) for DR progression. The progression of DR was defined by the procedure code of panretinal photocoagulation, intravitreal injection or vitrectomy; or the addition of diagnostic code of vitreous hemorrhage, retinal detachment, or neovascular glaucoma. The age and sex-adjusted HR of DR progression was 0.74 for DPP4i add-on group compared with SU add-on group (95% confidence interval [CI], 0.62 to 0.89). This lower risk of DR progression remained significant after additional adjustments for comorbidities, duration of metformin therapy, intravitreal injections and calendar index year (HR, 0.80; 95% CI, 0.66 to 0.97). This population-based cohort study showed that the use of DPP4i as add-on therapy to metformin did not increase the risk of DR progression compared to SU.